Dampak Pertumbuhan Dana Pihak Ketiga, Pertumbuhan Kredit, Risiko Kredit dan Financial Technology terhadap Profitabilitas Bank Konvensional Masa Pandemi Covid-19 - Manalu, Novita Yenni Boang; Moeljadi, Moeljadi; Widiastuti, Ni Putu Eka (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study was conducted with the aim of analyzing the impact of third party funds (DPK), credit growth and financial technology on the profitability of conventional banking during the Covid-19 pandemic. The population is conventional banking in Indonesia listed on the IDX in 2018-2021. Sample selection used purposive sampling technique. The secondary data source used taken from financial reports of samples for the 2018-2021 period and is analyzed using panel data regression technique. The findings indicated that DPK and credit growth have an insignificant effect on bank profitability, credit risk has a negative impact on bank profitability, while financial technology is proven to have a significant effect on bank profitability. The implication of the results is to provide an overview of the impact of DPK growth, credit growth, credit risk, and financial technology on the profitability of conventional banking during the Covid-19 outbreak.